Pelatihan propagasi anggrek skala rumah tangga kepada kelompok wisata di kawasan Sapuangin, Merapi, Klaten - Mursyanti, Exsyupransia; Nelsiani To’bungan; Pantalea Edeilweiss Vitara; Bernardus Boy Rahardjo Sidharta; Patricius Kianto Atmodjo; Sendy Junedi; Stefani Santi Widhiastuti (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
Sapuangin area is one of supporting areas for Mount Merapi National Park (TNGM). The endemic Merapi orchid is widely cultivated by people in the Sapuangin, using conventional cultivation. Sapuangin’s youth, who are members of a tourism group (POKWIS) have never received training regarding orchid propagation using in vitro culture principles. This is important to support orchid conservation activities carried out by POKWIS in the Sapuangin greenhouse. Based on requests from the community, lecturers and educational laboratory staff concentrating on Technobio-Industrial Studies, Faculty of Biotechnology, Universitas Atma JayaYogyakarta, provided a series of training on in vitro orchid culture, for household scale. This activity is expected to provide knowledge and skills regarding orchid cultivation techniques for the community. The activity was held on 12-20 December 2023. The training activity was divided into several topics, namely introduction to orchid types and their uses, principles of in vitro orchid culture, introduction to tools, methods for sterilizing and sowing orchid seeds, pollination/pollination, overplanting, and acclimatization. The training carried out can provide additional knowledge for the community regarding in vitro orchid cultivation techniques. The implementation of the training was considered very useful and by community needs, the training resource was competent, the implementation time was by the plan, and was supported by complete facilities and infrastructure. The community hopes for ongoing guidance and assistance regarding orchid propagation in the future.